Role of agripreneurship in creating youth employment in the Sekhukhune District Municipality, Limpopo Province, South Africa - Ramushu, Mashego Maggie (My University, 2021)
Agriculture is an important sector that promotes food security in every country, and it contributes significantly to the economy of South Africa. There will be no food or clothing if agriculture does not exist. Agriculture accounts for 2.2% of Limpopo Province's economy. According to studies, it also contributed a large proportion to job creation. South Africa exports some of its produce to other countries, increasing the country's export level and, as a result, the Gross Domestic Product (GDP). Therefore, there is a need to adapt to new ways of conducting agriculture in order to operate it as a profitable business. Agripreneurship, as entrepreneurship in agriculture, encompasses both primary and secondary agriculture. Ploughing, farming, and mixed agriculture are examples of primary agricultural activities, while secondary agricultural activities include agro-processing and tertiary agricultural business such as agricultural marketing and agro-transportation. The study examines the role of youth in agripreneurship in creating employment opportunities in the Sekhukhune District Municipality. The unemployment rate in the Sekhukhune region and in South Africa is rising. This is a significant concern for the government; thus, the study examines the extent to which agripreneurship can help to reduce or alleviate unemployment. The challenges that youth in agripreneurship face in creating employment through agripreneurship, as well as the benefits, are also investigated. The qualitative research method was used to investigate youth perceptions of agripreneurship and the role of youth in agripreneurship in creating employment. Since the study's target population was small, census sampling was used; that is, fifteen (15) agripreneurs within the boundaries of the Sekhukhune District. This study reports on the findings of the study about the role of youth agripreneurship in job creation and the perception of youth towards agripreneurship in Sekhukhune District, Limpopo. The study discovered that youth engaged in agripreneurship in the Sekhukhune District Municipality played a substantial role in creating employment ranging from casual to permanent, and that youth perceived agripreneurship to have high employment prospects. The study also revealed challenges associated with youth in agripreneurship, such as a lack of capital, market, and extension officer support, as well as environmental factors such as storms.
Thesis (MBA.) -- University of Limpopo, 2021
Keywords: Youth employment; Agrpreneurship; Sekhukhune District Municipality; Youth -- Employment -- South Africa; Job creation -- Congresses